PENDIDIKAN KARAKTER DI PESANTREN DALAM PEMIKIRAN K.H. MA. SAHAL MAHFUDH - Wahrodi Wahrodi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2013)
This paper would like to analyze how the positioning of pesantren and Kiai in viewing education through out Kiai Sahal perspective. As thinker from the circle of Pesantren, Kiai Sahal was become an original thinker and jurist from pesantren. According to Kiai Sahal, education interpreted as the process of implementing a good habit and characteristic in the behavior of student. According to him, education is not only the process of transfer of knowledge but also the process of shaping student to be insan al-kamil and akram. Finally, this paper conclude some views from the thought of Kyai Sahal. Fisrt, Education according to Kyai Sahal the process to inhabit student the perfect characteristic throught guidance and role so that the student have malakah (isntink) and awareness to do good did. Second, the term of tafaqquh fi> ad-di>n according to Kyai Sahal is interpreted as managing all the capability of student so that they can be get hapyness in this world and here after. Third the goal of Islamic education within pesantren according to Kyai Sahal is to get a happynes in this world and here after (Sa‘a>dah fi> ad-da>rain). Fourth, from the progeressive thinking of Kyai Sahal, education has some basics; religion, social, politic or policy, psychological view and philoshophy. Finally the goal of education in pesantren is to combine between llm and aml.